2015
DOI: 10.1016/j.jbspin.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Rilonacept in the treatment of subacromial bursitis: A randomized, non-inferiority, unblinded study versus triamcinolone acetonide

Abstract: While improvement in QuickDASH and pain was noted with a single intrabursal injection of rilonacept at 4 weeks, injection with triamcinolone acetonide was more efficacious. This trial was registered with www.clinicaltrials.gov (NCT01830699).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…The optimal dosage, concentration and volume in the subacromial space are still controversial (9). There are several studies on the combinations of corticosteroid suspension with either high-volume (23,24) or lowvolume (25). A study involving two groups of 26 patients reported that 3 cc lidocaine + 1 cc triamcinolone and 9 cc lidocaine + 1 cc triamcinolone yielded comparable results during a follow-up of 8 weeks (9).…”
Section: Discussionmentioning
confidence: 99%
“…The optimal dosage, concentration and volume in the subacromial space are still controversial (9). There are several studies on the combinations of corticosteroid suspension with either high-volume (23,24) or lowvolume (25). A study involving two groups of 26 patients reported that 3 cc lidocaine + 1 cc triamcinolone and 9 cc lidocaine + 1 cc triamcinolone yielded comparable results during a follow-up of 8 weeks (9).…”
Section: Discussionmentioning
confidence: 99%
“…В обеих группах было достигнуто статистически значимое уменьшение боли через 4 нед., более выраженное в группе триамцинолона (p = 0,044). С учетом высокой частоты эпизодов диареи и головной боли триамцинолон продемонстрировал некоторые пре-имущества по сравнению с рилонацептом для лечения больных с субакромиальным бурситом [47].…”
Section: таблицаunclassified
“…Generally, when compared to low-volume CI, HVCI of lidocaine is associated with a higher risk of consequences, in particular, soft tissue irritation. And furthermore, when corticosteroids are at lower concentrations, the steroid effects decrease, which should only be acceptable if being using for therapeutic purposed 8 . In the case of patient, the pain and functional outcomes of the corticosteroid injection were satisfactory.…”
Section: Introductionmentioning
confidence: 99%